Regional economic outlook navigating stormy waters. (World economic and financial surveys., 2011)
Following a strong showing in early 2011, the economies across Europe now face the prospect of a pronounced slowdown, as global growth has softened, risk aversion has risen, and strains in Europe's sovereign debt and financial markets have deepened, according to this issue of the Regional Economic Outlook for Europe. Downside risks are significant, and a further deepening of the euro area crisis would affect not only advanced Europe, but also emerging Europe, given its tight economic and financial ties. The policy stance in advanced Europe will need to be adapted to reflect the weakening and t.